Pemikiran Shaykh ‘Abdullah ‘Arif tentang doktrin Nur Muhammad dalam kitab Bahr al-Lahut / Amin Che Ahmat - Amin , Che Ahmat (2012)
This dissertation is put forth in order to analyze the thought of Shaykh `Abdullah `Arif on the doctrine of Nur Muhammad in his work Bahr al-Lahut. Overall this study adopted the method of library research. Six chapters are being discussed in this research. The first chapter describes the introduction to the entire study performed and objectives intended to be achieved. The second chapter discusses the stature of Shaykh `Abdullah `Arif and Bahr al-Lahut manuscript. The third chapter discusses on the effort on knowledge editing and translating new text edited on Bahr al-Lahut. The fourth chapter elaborates on the theoretical framework of the study, which includes a discussion on the doctrine of Nur Muhammad in Tasawuf, in conjunction with the evidence from the al-Qur’an and the al-Hadith, pro and contra views on Nur Muhammad, and the doctrine of Martabat Tujuh. Meanwhile, the fifth chapter contains the analysis of the whole thought of Shaykh `Abdullah `Arif from his work Bahr al-Lahut on Nur Muhammad. Finally, this research ended with a concluding chapter containing the summary of the research findings and suggestions. To conclude, the results showed that Shaykh ‘Abdullah ‘Arif’s views contain a discussion on natural creation.